SINERGIRITAS BUMDES DAN POKDARWIS DALAM PENGELOLAAN DESA WISATA - I Nengah Aristana; I Nengah Subadra; Ni Made Hartini (Synergy and Society Service, 2022)
The autonomy policy is the focus of the central and regional governments, the autonomy policy is basically the delegation of rights, authorities, and obligations to the regions in order to be able to regulate and manage their own government affairs for the benefit of the community. Along with the development of the autonomy policy, the government feels that it is time for the village to implement autonomy to accelerate village economic growth. Duda Timur Village is one of the villages in the Karangasem Strait District, Bali which is currently developing the potential of a tourist village. The development of village tourism is also supported by the existence of creative industries in Duda Timur Village. So that through the synergy of Pokdarwis and BUMDes, it is hoped that this can be the right step that can accelerate the growth of the village economy and can accelerate government programs related to autonomy.